Speech Act and the Analysis for English Text Book Material Development at Eleven Grade of Vocational High School - Santoso, Algajaladre Nadya; Affini, Laily Nur (ETERNAL (English Teaching Journal), 2019)
The aim of this research is to recognize the types of speech acts, conveyed by an English teacher at a vocational highschool, using Searle?s  theory and to discover the dominant kinds of speech act employed by the teacher. The researcher also there were additional utterances used by the tecaher in showing learning movement. The research methodology is descriptive-qualitative research. In this research, the researcher found that there are three kinds of speech act uttered by the teacher; they are directives, representative and  expressive. The reseacher calculated the data finding and found 397 utterances. The data found that there are 246 directives utterances with the percentage is 61,96% , 45 representative  untterances with the percentage is 45%, and 6 expressive utterances with the precentage 1,51% . The most obtrustive is directives speech act (61,96%) and the most seldom is expressives speech act (1,51%). The most obtrustive is directives because the teacher often used directives (questioning) to handle the students in the classroom and make sure that the students understood the aims of the English material.